International politics and performance critical aesthetics and creative practice - Edkins, Jenny; Kear, Adrian 1970- (Interventions, 2013)
The book's focus throughout is on the materiality of performance practices-on the politics of making, spectating, and participating in a variety of modes as political actors and audiences-whilst also seeking to explicate the performative dynamics of creative and critical thinking. Structured thematically and framed by a detailed introduction and conclusion, the focus is on producing a dialogue between contributors and providing an essential reference point in this developing field.